Study of Resistance on Orchids Induced Rhizoctonia to ORSV Based on Secondary Metabolite Analysis - Mahfut Mahfut; Widi Aryani; Tundjung Tripeni Handayani; Sri Wahyuningsih (Universitas Khairun, 2022)
Dendrobium discolor and Phalaenopsis amabilis are in high demand because of their beautiful shape, color, texture, and flower arrangement. The current obstacle to orchid cultivation is infection with Odontoglossum ringspot virus (ORSV). One of the efficient ways to control the infection of this pathogen and does not cause an impact on the environment is to use Rhizoctonia mycorrhizae. Mycorrhizal relationship with plants will form induced resistance. Plants resulting from induced resistance will induce secondary metabolite, namely peroxidase enzymes. This type of secondary metabolites will prevent the growth and development of pathogens and plants become resistant to pathogenic infections. The purpose of this study was to determine differences in peroxidase enzyme activity and differences in resistance to P. amabilis and D. discolor after Rhizoctonia induction against ORSV infection. This research was carried out in several stages, namely plantlet preparation, mycorrhizal inoculation, mycorrhizal inoculation, and peroxidase enzyme activity analysis using a UV Vis spectrometer at a wavelength of 420 nm. The results showed that D. discolor had a higher peroxidase enzyme activity than P. amabilis. In the treatment application factor, the peroxidase enzyme activity was the highest in the Mycorrhizal Virus treatment compared to the Mycorrhizal and Virus treatments. This study showed that D. discolor was more resistant to ORSV infection than P. amabilis. and the application of Mycorrhizae proved to be successful in increasing the activity of the peroxidase enzyme as a response to plant protection against viral infections.